Neuroprotective Effects of Green Tea (Camellia Sinensis) and Broccoli (Brassica Oleracea) Extracts in an In Vitro Model of Multiple Sclerosis - Taha Fathallah, Sara (AUC Knowledge Fountain, 2023)
Multiple Sclerosis (MS) is a neurodegenerative autoimmune disease in which the immune system attacks the central nervous system (CNS) resulting in demyelination. Currently, there is no specific treatment for MS. Here, we propose testing the neuroprotective potential of Green tea (Camellia sinensis), and Broccoli (Brassica oleracea) extracts in an in vitro model of multiple sclerosis. Methods and Results: Green tea and Broccoli plant extracts were analyzed with GC-MS and tested for their neuroprotective effects in an in vitro MS model using Cuprizone (CPZ) on the Human neuroblastoma SH-SY5Y cell line. Cell viability assays proved the safety of the extracts on SH-SY5Y cells and their protective effect against CPZ. MMP-3, IL-1β, HIF-1α, NF-κB, and miRNA-124-3p gene expressions were measured by qRT-PCR. Broccoli plant extract significantly increased the expression of neuroprotective HIF-1ɑ and NF-κB in CPZ-treated cells. Both Green Tea and Broccoli extracts significantly reduced the expression of the inflammatory MMP-3 and IL-1β in CPZ-treated cells. The expression of neuroprotective miRNA 124-3p was significantly reduced in CPZ-treated cells and both extracts had no effect on its expression level. Conclusion: Broccoli extract exerted better neuroprotective effects as it significantly reduced inflammatory cytokines MMP-3 and IL-1β expression, and increased the expression of neuroprotective genes NF-κB and HIF-1α. enhanced the expression of the neuroprotective mRNA and decreased the expression of the inflammatory ones. In contrast, Green tea only exerted an effect against MMP-3 and reduced its expression. Both Green tea and Broccoli plant extracts However, they had no significant effect on miR-124-3p. These extracts proved to be neuroprotective in vitro, and proved their potential for further use in more complex models of MS. These extracts are available all over the world and are cheap, which makes them excellent candidates for use in future clinical trials. However, more studies are needed to identify their molecular targets.